PENGARUH PROFITABILITAS, UMUR PERUSAHAAN DAN UKURAN PERUSAHAAN TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN PERUSAHAAN - Widia Astuti; Teguh Erawati (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2018)
Financial information will have benefits if delivered on time to the wearer who is closely related to the agency theory (agency theory) where in the theory of this agency explained that the owner oversees the agency (employee) to perform more efficient performance. The value of timeliness of financial reporting is important for the level of benefit of the report. This study aims to test the profitability, age of the company and the size of the company to the timeliness of corporate financial reporting. The sample of this study consists of 13 food and beverage companies with 65 financial report data listed on the Stock Exchange 2012-2016. To test the hypothesis, used secondary data with purposive sampling method. Data analysis techniques used logistic regression analysis. After the data in the analysis, found that the profitability variable has a significance value of 0.045 means that the hypothesis X1 positive effect on timeliness of corporate financial reporting due to the significance value less than 0.05. Variable of company age have significance value equal to 0,066 and company size have significance value equal to 0,412 meaning hypothesis X2 and X3 have no effect to variable Y because significance value greater than 0,05.